2019
DOI: 10.12659/aot.911923
|View full text |Cite
|
Sign up to set email alerts
|

Patients Treated for Central Airway Stenosis After Lung Transplantation Have Persistent Airflow Limitation

Abstract: Background Although central airway stenosis (CAS) is a common complication after lung transplantation, its consequences have been poorly evaluated. The objective of our study was to evaluate the impact of CAS on lung function after lung transplantation. Material/Methods All lung transplant recipients from June 2009 to August 2014 in a single center (Strasbourg, France) were retrospectively reviewed. Results A total of 191 lung transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
10
0
2
Order By: Relevance
“…Our study revealed that in patients who required ≥1 BI during their first post-transplant year, spirometry parameters were statistically significantly lower than in patients who did not need such bronchoscopic treatment. A similar finding was reported by Mazzetta et al [ 8 ], who found that patients with central AS so severe it required BI had lower FEV 1 (L) and FEV 1 /FVC at 18-month follow-up (81±13% versus 61±14%, P <0.001).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study revealed that in patients who required ≥1 BI during their first post-transplant year, spirometry parameters were statistically significantly lower than in patients who did not need such bronchoscopic treatment. A similar finding was reported by Mazzetta et al [ 8 ], who found that patients with central AS so severe it required BI had lower FEV 1 (L) and FEV 1 /FVC at 18-month follow-up (81±13% versus 61±14%, P <0.001).…”
Section: Discussionsupporting
confidence: 88%
“…We also reported a statistically significant difference between our study groups in FEV 1 (%) between our study groups (81±27% versus 54±21%, P <0.001) and FEV 1 /FVC (78±18% versus 62±32%, P =0.004). Mazzetta et al also showed that CAS does not affect the survival of lung transplant recipients [ 8 ]. That is supported by a paper published by Shofer et al [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleeve resections have been successfully utilized for these complex situations 2‐4 . We preferred to preserve the entire graft to prevent long term decline in lung function as observed in patients with central airway stenosis 7 …”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] We preferred to preserve the entire graft to prevent long term decline in lung function as observed in patients with central airway stenosis. 7…”
Section: Discussionmentioning
confidence: 99%